INSPIRASIQU (INOVASI PEMBELAJARAN FISIKA BERBASIS SIMULASI DAN QUOTE): SEBUAH PENDEKATAN REFLEKTIF - Wulandari, Arum (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
INSPIRASIQU is a qualitative "best practice" approach that integrates the use of reflective quotes with interactive PhET (Physics Education Technology) simulations to create more relevant and meaningful physics learning experiences. This approach aims to bridge students' cognitive and affective domains and also foster their critical and reflective thinking skills.The implementation method begins with presenting reflective quotes to stimulate curiosity and activate prior knowledge. Subsequently, students explore physics concepts, such as kinematics and basic mechanics, using PhET simulations, which allow for direct manipulation of variables. The final stage involves reflection and group discussion to connect the simulation results with the reflective quotes and real-life experiences.The results of the study show an improvement in student engagement, conceptual understanding, and reflective attitudes. Students became more enthusiastic and motivated as a result of the observation. Students also reported that the quotes helped them "associate physics with real-life aspects," making the concepts feel more relevant and easier to understand.In conclusion, the integration of PhET simulations and reflective quotes has proven effective in enhancing student engagement, understanding, and reflective attitudes toward the physics material.